Secrets of Tamarind - Aguiar, Nadia (New York : Feiwel and Friends, 2011)
Four years after leaving the lost island of Tamarind, Maya, Simon, and Penny Nelson return to stop the Red Coral Project, a sinister group mining the magical mineral ophalla there and, in the process, ruining the magnificent island.
Kirkus Review
Kirkus Review, June 2011
6.4
5-8.
5-8
Keywords: Brothers and sisters -- Juvenile fiction; Environmental degradation -- Juvenile fiction; Islands -- Juvenile fiction; Magic -- Juvenile fiction; Mines and mineral resources -- Juvenile fiction; Adventure and adventurers -- Fiction; Brothers and sisters -- Fiction; Environmental degradation -- Fiction; Islands -- Fiction; Magic -- Fiction; Mines and mineral resources -- Fiction; Adventure fiction; Environmental degradation -- Fiction; Islands -- Fiction; Magic -- Fiction; Mines and mineral resources -- Fiction; Siblings -- Fiction; Adventure fiction